Cytomegalovirus gastritis: Clinicopathological profile. Issue 6 (June 2021) - Yeh, Pai-Jui; Chiu, Cheng-Tang; Lai, Ming-Wei; Wu, Ren-Chin; Kuo, Chia-Jung; Hsu, Jun-Te; Su, Ming-Yao; Le, Puo-Hsien
Abstract: Background: Cytomegalovirus (CMV) gastritis is occasionally reported in case reports and limited case series. Up to now, it is the largest and most comprehensive retrospective study of CMV gastritis. Methods: All patients who were histologically diagnosed with CMV gastritis at Linkou Chang Gung Memorial Hospital between January 2000 and April 2020 were included. Patients were divided into two groups according to immunity. Between-group differences in characteristics, manifestations, endoscopic features, prognostic factors, and outcomes were analyzed. The main endpoint was 3-month mortality. Results: A total of 54 patients (34 immunocompromised, 20 immunocompetent) were enrolled. Common presentations included gastrointestinal bleeding (35.2%), abdominal pain (33.3%) and fever (31.5%). The endoscopic features included ulcer (88.9%) and inflammation (11.1%). The 3-month mortality rate was 20.4% and overall mortality rate was 40.7%. Acute kidney injury was the only independent risk factor for 3-month mortality (OR 53.89, 95%CI 1.56–1861.73, p  = 0.027). Anti-viral therapy and host immune status did not affect 3-month mortality. Conclusion: Both immunocompromised and immunocompetent patients with CMV gastritis have high mortality rates, without significant between-group differences. Acute kidney injury is the only independent predictive factor for 3-month mortality. Prevention of acute kidney injury may possibly improve the 3-month mortality rate.